DEVELOPMENT OF INTERCULTURAL COMMUNICATION COMPETENCE OF CADETS USING INTERACTIVE METHODS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Great importance should be attached to the rapid development of priority tasks that need to be solved in the implementation of the socio-economic development of the Republic of Uzbekistan. In this regard, the Decree of the President of the Republic of Uzbekistan dated October 8, 2019 "On approval of the consortium for the development of the higher education system of the Republic of Uzbekistan until 2030" PD-5847 prioritizes the development of the field of education along with "increasing the share of independent education hours, independent education in students, critical and creative thinking, systematic analysis, formation of entrepreneurial skills, implementation of methods and technologies aimed at strengthening competences in the educational process, implementation of the educational process in ensuring the implementation of the task of promoting the formation of skills, in this case, the wide implementation of advanced educational technologies, educational programs and educational materials based on international educational standards in the educational process"[1] shows the need to modernize the methodological bases of teaching foreign languages.